Learning to forget the anti-memoirs of modernity - Gupta, Dipankar, 1949- (New Delhi ; Oxford : Oxford University Press, 2005)
This title argues that it may not be sufficient to equate the idea of modernity only with morphological attributes as technology science and industrialisation, particularly in the context of developing societies such as India. It also introduces the conceptual category of inter-subjectivity to analyse various facets in Indian social life.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Intersubjectivity; Memory -- Social aspects; Culture -- Philosophy; Philosophy and social sciences